DOI: 10.11606/d.10.2003.tde-07062004-155248
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição ao estudo da hepatite A em primatas neotropicais

Abstract: Catão-Dias, meu querido orientador, por aceitar me orientar. Sua compreensão, auxílio, amizade e apoio, tanto na esfera profissional como na pessoal, foram de fundamental importância neste período de trabalho em conjunto. Agradeço-o especialmente por ter me ensinado tanto durante todos esses anos. Ao Paulo, meu marido, por sempre ter me icentivado, não deixando que eu desanimasse nos momentos mais críticos. Agradeço também sua paciência e auxilio na área de informática, especialmente nos momentos de desespero,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…The results from this study have shown that 4.5% (5/107) of the serum samples derived from free-ranging NTPs were positive for anti-HAV IgG antibodies, and represent the first published investigation that evaluated the risk of NTPs being infected by HAV in Brazil. However, the results of a study that determined the occurrence of HAV in captive non-human primates (NHPs) demonstrated that 4.5% (5/125) of NHPs from the State of Riode Janeiro and 7.6% (17/233) of NHPs maintained within zoological parks of the State of São Paulo were seropositive for anti-HAV IgG 24 . These results suggest that captive and free-ranging NTPs from distinct geographical regions of Brazil were exposed to HAV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from this study have shown that 4.5% (5/107) of the serum samples derived from free-ranging NTPs were positive for anti-HAV IgG antibodies, and represent the first published investigation that evaluated the risk of NTPs being infected by HAV in Brazil. However, the results of a study that determined the occurrence of HAV in captive non-human primates (NHPs) demonstrated that 4.5% (5/125) of NHPs from the State of Riode Janeiro and 7.6% (17/233) of NHPs maintained within zoological parks of the State of São Paulo were seropositive for anti-HAV IgG 24 . These results suggest that captive and free-ranging NTPs from distinct geographical regions of Brazil were exposed to HAV.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, seropositivity to HAV in captive NHPs seems to vary in different geographical locations. Additionally, SETZER 24 evaluated the presence of HAV in captive and free-ranging NHPs, and demonstrated that only captive NHPs were seropositive to IgG-anti HAV antibodies. Moreover, a recent study that evaluated the presence of zoonotic disease in captive NTPs from the state of Pará , northern Brazil, demonstrated that 12% of the 29 NTPs evaluated were seropositive for anti-HAV antibodies, but without specific reaction to IgG or IgM anti-HAV antibodies 16 .…”
Section: Discussionmentioning
confidence: 99%